(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article is devoted to the development of theoretical foundations of the methodological system of development of teaching and research skills of students and its model, to the illumination of psychological and pedagogical aspects of the teacher’s and student’s activity in the process of development of teaching and research skills of students.